A construção da forma n A Hora da Estrela, de Clarice Lispector - Spinelli, Daniela (2008)
The main purpose of this Master's Degree thesis, in which the object of investigation is Clarice Lispector s The Hour of the Star, is to analyse the relationship between Rodrigo S.M. and Macabéa, respectively the narrator and the protagonist of this novel. In light of the established criticism of this piece of literature, we attempt to uncover what innovative ideas the story of Macabéa brings to the Clarice Lispector literary project. The Hour of the Star re-calibrated the literary form developed by the writer the moment the misery of Macabéa became the central theme of the novel. Through careful examination of the events of Macabéa s life, a Young woman, orignally from the northeast of Brazil, that works as typist despite being semi-illiterate, who later lives in Rio de Janeiro, we attempt to better comprehend the perspective of Rodrigo S.M., narrator/character of the novel. Following this examination it becomes evident that the narrator is committed to material issues such as class, culture and his profession as a writer. One issue faced by Clarice Lispector, as with other writers, is to find a literary form with which to represent this historic time in Brazilian history that was marked by a military dictatorship. Far from only being a discussion centered on the representation of material content, The Hour of the Star is the moment in Clarice Lispector s body of literary work where her writing gains weight and density in a mature and conscience way. In this context, it is necessary to analyse Rodrigo S.M. as a formal solution of a novel that accomplished a settlement with its time and its social experience. The reader of the novel, cannot forget that the caracters of The Hour of the Star, as well the narrator are, for Clarice Lispector, figures of a piece of literarture that eagerly desire to respond to its time and to the social experience that inspired her